Blended Extensibility of Cyber Forensics (International Journal of Engineering and Computer Science, 2018)
For today’s attack-prone and vigorously developing world, network security is as important as eating food. This is because any pinch of vulnerable source (whether self or by-attacker) could adversely affect the end-user data, information as well as all useful assets. Cyber Forensics proves to be an advantage in presenting the evidence, against the court of law, if required, in defence of an attack. This can also help the end-user become more cautious and secure to repress against any kind of vulnerabilities. Generally, not many people are aware about it, which is the strongest reason for an attacker to commit the attack again.